2016
DOI: 10.1037/dev0000196
|View full text |Cite
|
Sign up to set email alerts
|

Numerical cognition explains age-related changes in third-party fairness.

Abstract: Young children share fairly and expect others to do the same. Yet little is known about the underlying cognitive mechanisms that support fairness. We investigated whether children's numerical competencies are linked with their sharing behavior. Preschoolers (aged 2.5-5.5) participated in third-party resource allocation tasks in which they split a set of resources between 2 puppets. Children's numerical competence was assessed using the Give-N task (Sarnecka & Carey, 2008; Wynn, 1990). Numerical competence-spec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
45
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 49 publications
(54 citation statements)
references
References 39 publications
(63 reference statements)
8
45
1
Order By: Relevance
“…Prior work points to several correlates of cardinality that may be most relevant to active resource distribution: acquiring knowledge of the cardinal principle may increase the precision through which children perform intuitive division operations on the resources (McCrink & Spelke, ), provide a tool through which children can count out equal sets (Sarnecka & Wright, ) or help participants identify when sharing errors occur (Muldoon, Lewis, & Berridge, ). Consistent with our findings, in the latter two cases, cardinality, rather than subitizing or knower‐level knowledge, relates to these developments (see also Chernyak et al., ; Jara‐Ettinger et al., ; Moore, vanMarle, & Geary, ).…”
Section: Discussionsupporting
confidence: 91%
See 4 more Smart Citations
“…Prior work points to several correlates of cardinality that may be most relevant to active resource distribution: acquiring knowledge of the cardinal principle may increase the precision through which children perform intuitive division operations on the resources (McCrink & Spelke, ), provide a tool through which children can count out equal sets (Sarnecka & Wright, ) or help participants identify when sharing errors occur (Muldoon, Lewis, & Berridge, ). Consistent with our findings, in the latter two cases, cardinality, rather than subitizing or knower‐level knowledge, relates to these developments (see also Chernyak et al., ; Jara‐Ettinger et al., ; Moore, vanMarle, & Geary, ).…”
Section: Discussionsupporting
confidence: 91%
“…Initial analyses showed that girls were more likely to choose the equal split than boys, consistent with prior work finding that girls show a greater aversion to inequity (Chernyak et al., ; McAuliffe et al., ). Therefore, we control for gender in all of our subsequent models.…”
Section: Resultssupporting
confidence: 77%
See 3 more Smart Citations